Virtual benchmarking and model continuity in prototyping embedded multiprocessor signal processing systems. - Janka, R.S (IEEE Transactions on software engineering)
The complexity of hardware/software codesign of embedded real-time signal processing systems can be reduced by rapid system prototyping (RSP). However, existing RSP frameworks do not provide a sound specification and design methodology (SDM) because they require the designer to choose the implementation target before specification and design exploration and they do not work together coherently across development stages. This paper presents a new SDM, called MAGIC, that allows the designer to capture an executable specification model for use in design exploration to find the optimal multiprocessor technology before committing to that technology. MAGIC uses a technique called "virtual benchmarking," for early validation of promising architectures. The MAGIC SDM also exploits emerging open-standards computation and communication middleware to establish model continuity between RSP frameworks. This methodology has been validated through the specification and design of a moderately complex system representative of the signal processing domain: the RASSP Synthetic Aperture Radar benchmark. In this case study, MAGIC achieves three orders of magnitude speedup over existing virtual prototyping approaches and demonstrates the ability to evaluate competitive technologies prior to implementation. Transfer of this methodology to the system-on-a-chip domain using Cadence's Virtual Component Codesign infrastructure is also discussed with promising results.